Avalia????o da dor e da atividade eletromiogr??fica do m??sculo trap??zio em pacientes com cervicalgia inespec??fica pr?? e p??s irradia????o com laser baixa pot??ncia: um estudo cruzado, controlado, randomizado duplo cego - Calamita, Simone Aparecida Penimpedo (2015)
The nonspecific neck pain (CI), can provide great personal suffering has as a possible consequence, disability and reduced quality of life and labor productivity, and generate high social and economic costs for patients and society. Thus, the aim of this study was to evaluate the immediate effect of low power laser irradiation (LBP) on the electromyographic (EMG) activity of the trapezius muscle descending fibers (PDT) in patients with IC. This was a crossover design, controlled, randomized double-blind, composed of 20 individuals with IC. Each individual received a radiation session with LBP continuous mode (wavelength: 880 nm, power of 30mW, power density: 1.07 W / cm; beam area: 0,028 cm2; energy density: 72J / cm2, energy total per point: J 2, irradiation time: 67 s) and LBP treatment with placebo (LBPP) (no dosimetric parameters). Randomization of the participants compared to the LBP or LBPP treatment was performed by drawing. The effects of therapy were verified through the Verbal Numeric Scale of Pain (EVND), it measures the area of pain, and the electromyographic activity of the PDT muscle. In the pre and post treatment with LBP and LBPP comparison was no significant change observed in pain intensity obtained by EVND (F = 1.93; p = 0.17) regardless of the type of intervention (treatment group vs) (F = 0, 02, p = 0.96) as well as the dad or area (p = 0.11) and LPBP (p = 0.06). An increase and a significant decrease in nerve conduction velocity and amplitude of the EMG signal respectively, were found in the treatment LBPP while no changes were found in for treatment with LBP. In this study, a single laser dose not provide analgesia to patients with IC however, the electromyographic analysis showed an ergogenic effect on muscle after PDT treatment.